Implementing Kurikulum Merdeka in Informatics learning at SMAN 7 Bandung - Kiagus Muhammad Ryan (Hipkin Journal of Educational Research, 2025)
This article discusses the implementation of the Informatics subject within the framework of the Merdeka Curriculum at SMAN 7 Bandung. The study is motivated by a national curriculum reform that introduces Informatics as a compulsory subject in high schools to strengthen students' digital competencies in response to rapid technological development. The aim of this research is to describe the implementation strategies of the Informatics subject and identify the challenges faced by SMAN 7 Bandung, particularly regarding limitations in human resources and infrastructure. This qualitative research was conducted through interviews with the vice principal of curriculum and the informatics teacher. This research aims to reveal that implementation has been carried out gradually, accompanied by adjustments in teaching methods and the use of technology suited to the school’s conditions. The main challenges include a shortage of Informatics teachers and insufficient facilities. Nevertheless, SMAN 7 Bandung has made efforts to adapt the learning process to remain relevant and effective through active learning approaches and the use of available technologies. This study contributes to curriculum research in Indonesia, particularly in the integration of technology-based learning in Informatics education.   Abstrak Artikel ini membahas implementasi mata pelajaran Informatika dalam kerangka Kurikulum Merdeka di SMAN 7 Bandung. Penelitian ini dilatarbelakangi oleh kebijakan kurikulum nasional yang menempatkan Informatika sebagai mata pelajaran wajib di SMA untuk memperkuat kompetensi digital peserta didik dalam menghadapi perkembangan teknologi. Tujuan penelitian ini adalah untuk mendeskripsikan strategi implementasi mata pelajaran Informatika serta tantangan yang dihadapi SMAN 7 Bandung, terutama terkait keterbatasan sumber daya manusia dan infrastruktur. Penelitian dilakukan dengan pendekatan kualitatif melalui wawancara dengan wakil kepala sekolah bidang kurikulum dan guru Informatika. Hasil penelitian menunjukkan bahwa implementasi dilakukan secara bertahap, disertai penyesuaian metode dan penggunaan teknologi yang relevan dengan kondisi sekolah. Tantangan utama meliputi keterbatasan jumlah guru Informatika dan sarana prasarana yang belum memadai. Meskipun demikian, SMAN 7 Bandung tetap berupaya menyesuaikan pembelajaran agar relevan dan efektif melalui pendekatan aktif dan pemanfaatan teknologi yang tersedia. Penelitian ini memberikan kontribusi terhadap kajian kurikulum di Indonesia, khususnya dalam konteks pengajaran Informatika berbasis teknologi. Kata Kunci: implementasi kurikulum; Kurikulum Merdeka; pembelajaran informatika